Context Prediction Analysis and Episodic Memory - Mizumori, Sheri J. (Frontiers in Behavioral Neuroscience, 2013)
Events that happen at a particular place and time come to define our episodic memories. Extensive experimental and clinical research illustrate that the hippocampus is central to the processing of episodic memories, and this is in large part due to its analysis of context information according to spatial and temporal references. In this way, hippocampus defines ones expectations for a given context as well as detects errors in predicted contextual features. The detection of context prediction errors is hypothesized to distinguished events into meaningful epochs that come to be recalled as separate episodic memories. The nature of the spatial and temporal context information processed by hippocampus is described, as is a hypothesis that the self-regulatory nature of hippocampal context processing is mediated by natural homeostatic operations and plasticity. The presence of context prediction errors by hippocampus is suggested to be valued by the midbrain dopamine system, the output of which is ultimately fed back to hippocampus to update memory-driven context expectations for future events. Thus, multiple network functions (both within and outside hippocampus) combine to result in adaptive episodic memories.